Pengembangan Media Pembelajaran Video Animasi Pada Materi Menulis Puisi Kelas X SMA - Siti Malahayati Ritonga; Ali; Deliani (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2022)
This study aims to: (1) Describe the Development Process of Canva Animation Video Learning Media Writing Poetry for Class X SMA, (2) Describe the Validity of Material Experts and Media Experts About Development of Learning Media Canva Animated Video Writing Poetry for Class X SMA, (3) Describe the Feasibility Canva Animation Video Learning Media Products for Class X High School Poetry Writing. Sources of data in this study in the form of a questionnaire. The type of data used is descriptive qualitative data as the main data collected through an instrument with a Likert scale. Respondents in this study were Material Experts and Media Experts. This research method is a deve lopment research using the Borg and Gall Model which was adjusted in 6 stages because it was still in a state of the Covid-19 pandemic, namely (1) needs analysis, (2) Product Specification Planning, (3) Product Design, (4) Product Validation. , (5) Product revision/improvement, (6) Dissemination. The material expert's response, obtained the average overall aspect of the material in the "adequate" category. This means that Canva's Poetry Writing animation video learning media with the help of the Canva application for class X high school students is feasible and valid to be applied to small groups or large groups.